PENGARUH PEMBINAAN, PELATIHAN DAN PENGEMBANGAN, PEMBERDAYAAN DAN PARTISIPASI TERHADAP KINERJA KARYAWAN - Fendy Levy Kambey; Suharnomo Suharnomo (Faculty of Economics and Business Diponegoro University, 2013)
Njonja Meneer company pointed out that the organization is already doing application coaching, training and development, empowerment and participation in the organizational practices. But in applying coaching and empowerment of the variable is still not carried out optimally. This is apparent from the results of the interviews also showed that employees in the performance of Njonja Meneer company is still low. The purpose of this study was to analyze the influence of coaching, training and development, empowerment and participation on employee performance in PT. Njonja Meneer. The sample used in the study were sixty people. Data analysis method used is multiple linear regression analysis using IBM SPSS 21. Sampling in this study based on terms the respondents established earlier that all employees and managers of high level from all fields who have worked at least six months and have experienced the process of training development, and has been involved (participating) in decision making in Njonja Meneer company. The results show that the coaching, training and development, empowerment and participation affect the performance of employees above fifty percent. From the results of the regression analysis training and development have the greatest influence on employee performaance. That means training and development at Njonja Meneer company already done well and have the most impact on employee performance than coaching, empowerment, and participation. While the smallest variable that affects employee performance is empowerment and coaching. Keywords: Coaching, Training and Development, Empowerment, Participation, Employee performance